Efficacy of AT in pre-eclampsia: a case-control prospective trial - Paternoster, Delia M.; Fantinato, Sara; Manganelli, Francesca; Milani, Massimo; Nicolini, Umberto; Girolami, Antonio (Thrombosis and Haemostasis, 2004)
Pre-eclampsia is an extremely severe condition. It is associated with vasospasm, activation of the coagulation system and abnormal haemostasis. In pre-eclamptic patients increased plasmatic concentrations of fibronectin, laminin, von Willebrand factor (VWF) and endothelin are observed. Experimental studies on rats have also shown that the doses of antithrombin III (AT) needed to mediate anti-inflammatory processes are much higher than those required to obtain the anti-coagulant effect. The study aimed to evaluate the clinical efficacy of treatment with high AT doses (HD) in comparison with standard doses (SD). The primary endpoint was the prolongation of pregnancy defined as time (in days) from enrollment to delivery and to assess the maternal bleeding at and after delivery. The secondary endpoint was to demonstrate a role for AT in controlling haemostasis at conventional doses, and the inflammatory state at higher doses. The biochemical parameters assessed were: AT activity (%), Fibronectin (Fn), Fibrinogen, D-dimer, Uricemia, Proteinuria 24h, Protein C Reactive (PCR), Granulocyte Elastase and Endothelin. This study included 23 pre-eclamptic women. Patients were randomly subdivided into two groups: 10 patients (“cases”) were treated with high doses of AT (6 vials: 3000 units) once daily for 5 days, or until delivery, while 13 women (“controls”) were treated with doses of AT sufficient to maintain at least 80% of the activity. High-dose therapy was associated with prolongation of pregnancy by 2.5 days more when compared with controls (p = 0.03; Mann-Whitney test). The incidence of clinical significant bleeding was lower in cases than in controls (mean 550 mL vs. 650 mL, respectively). Preventiveand conservative-type treatment of moderatesevere pre-eclampsia, based on the administration high doses of AT, allows a significant prolongation of pregnancy, and thus a better neonatal outcome, as well as less maternal intra-and post-operative bleeding. Fn, PCR and elastase levels (markers of inflammation) decrease in the HD group in comparison with SD group. In the HD group, the AT plasma levels were obviously higher both at the end of the treatment (p < 0.0001) and after delivery (p = 0.03), in comparison with SD group. The fibrinogen and D-dimer levels were above the reference interval in both groups. TPA and PAI 1 were found to be significantly raised in the course of pre-eclampsia. In conclusion, the biochemical findings support a role for AT in controlling the haemostasis at conventional doses, and the inflammatory state at higher doses.
Keywords: AT; pre-eclampsia; pregnancy